Child Problems as a Moderator of Relations Between Maternal Impulsivity and Family Environment in a High-Risk Sample. (23rd August 2016) - Friedman, Carly K.; Ryan, Stacy R.; Charles, Nora E.; Mathias, Charles W.; Acheson, Ashley; Dougherty, Donald M.
ABSTRACT: Objective : Previous studies have suggested that maternal characteristics are related to family environment; however, the relation between maternal impulsivity, in particular, and family environment is not well understood. As such, we examined direct relations between maternal impulsivity and family environment, as well as whether the relation between maternal impulsivity and family environment was moderated by child problems for sons and daughters. We hypothesized that child problems would moderate the association between maternal impulsivity and family environment. We also explored whether these associations differ for boys and girls. Method : Data from the initial visit of a longitudinal study was used for the current study. Participants included 297 youth (137 boys; 160 girls) of 10 to 12 years of age ( M = 10.99, SD = .84) and their mothers. The majority of the sample had a family history of substance use disorder ( n = 236). Results : Hierarchical linear regressions showed that for sons there was a significant interaction between maternal impulsivity and child problems on family environment. Maternal impulsivity was positively related to family environment problems among sons with few emotional and behavioral problems, but there was no significant correlation among sons with high problem levels. Among daughters, there was no significant interaction between maternal impulsivity and child emotional and behavioral problems on family environment. Conclusions : The results suggest that the association between maternal impulsivity and family environment may depend on problem level and child gender. Thus, addressing maternal impulsivity in therapy may benefit some families.